The United States’ Assault on Multilateralism: The Crisis in WHO, WTO and ICC - Yadav, Anita; Srivastva, Utkarsh (Faculty of Law, Universitas Brawijaya, 2024)
The culmination of the second world war marked the beginning of multilateral cooperation amongst nations of the world to achieve peace, security, economic prosperity, and social advancement. The United States led the international movement towards achieving common goals through multilateral efforts during that era. However, in recent years, the United States’ disenchantment with the principle of multilateral cooperation has become increasingly prominent. The authors have adopted descriptive analytical approach to analyse the unilateral actions taken by the United States against three multilateral organisations, namely, the World Health Organization, the World Trade Organization and the International Criminal Court, which have been at the forefront of the United States’ criticism. The article also critically evaluates the criticism by the United States against these organisations. Further, the authors have also explored the shortcoming in terms of the structure and functioning of these organisations. These organisations have long relied on the cooperation between their members to fulfil their mandates in addressing global challenges. The United States' actions against these organizations have demonstrated a disregard for multilateralism and a preference for the age-old dictum of ‘might is right’. The actions of the United States must also be seen from the lens of challenges it faces today, particularly from China and other emerging economies. Perhaps, the United States’ actions can be seen as an attempt to counter the diminishing giant syndrome. Thus, it is imperative for other nations to respond by reaffirming their commitment to collective action and shared responsibilities.